2006
DOI: 10.1111/j.1474-919x.2006.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Nest‐site fidelity and breeding success in White StorkCiconia ciconia

Abstract: Nest‐site fidelity is a life‐history trait of birds that may produce benefits in terms of fitness. We studied the relationship between breeding success and nest fidelity in the White Stork Ciconia ciconia. We also studied how other factors such as age, sex, habitat, colony size and productivity in previous breeding attempts might interfere with this relationship. Our results showed that pairs with higher fidelity rates also have lower failure rates, and that breeding failure and productivity in the previous se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 32 publications
1
53
2
1
Order By: Relevance
“…Bird attachment to previous nesting sites after breeding success could thus constitute one of the keys for the success of such programs (Groen 1993). Natal or breeding philopatry may indeed lead males and/or females in many species to return to or close to the same territories, even to the same nest sites, after succeeding in previous breeding attempts (Shields 1984;Gavin and Bollinger 1988;Haas 1998;Gauthier 1990;Simek 2001;Blackmer et al 2004;Catlin et al 2005;Fowler 2005;Vergara et al 2006). Following the assumption that the quality of a patch is reflected by its potential for allowing the production of offspring (Cody 1985), this study investigates the hypothesis that habitat selection by meadow passerines would be primarily influenced by the impact of mowing, i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Bird attachment to previous nesting sites after breeding success could thus constitute one of the keys for the success of such programs (Groen 1993). Natal or breeding philopatry may indeed lead males and/or females in many species to return to or close to the same territories, even to the same nest sites, after succeeding in previous breeding attempts (Shields 1984;Gavin and Bollinger 1988;Haas 1998;Gauthier 1990;Simek 2001;Blackmer et al 2004;Catlin et al 2005;Fowler 2005;Vergara et al 2006). Following the assumption that the quality of a patch is reflected by its potential for allowing the production of offspring (Cody 1985), this study investigates the hypothesis that habitat selection by meadow passerines would be primarily influenced by the impact of mowing, i.e.…”
Section: Introductionmentioning
confidence: 97%
“…The distance of reproductive dispersion in this study was 4.6 km, which is close to main natal dispersion in this study (4.21 km). Results from other research have also shown that natal dispersion is more common and individuals travel larger distances when compared to reproductive dispersion (Vergara et al 2006, Hénaux et al 2007, Itonaga 2009.…”
Section: Discussionmentioning
confidence: 89%
“…In Spain, about 80% of the examined individuals were faithful to their previous nests (Vergara et al 2006), while Chernetsov (2006 in a study of 73 individuals found only two cases with distances <10 km. Fidelity to the nesting site is considered a useful strategy that has been observed in other species in the family of Ciconiiformes, Anseriformes and Procellariiformes (Vergara et al 2006). The distance of reproductive dispersion in this study was 4.6 km, which is close to main natal dispersion in this study (4.21 km).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another advantage of dispersal is that it could reduce inbreeding (Greenwood et al 1978, Bauer 1987, Hansson et al 2002a These main patterns that affect site fidelity in birds can be summarized as: sex differences in fidelity within species with male biased return rates (Solonen 1979, Greenwood 1980, Payne & Payne 1993, Verhulst et al 1997, Schlossberg 2009); a tendency for greater fidelity in later life (Greenwood & Harvey 1982, Pärt 2001, Winkler et al 2004, Vergara et al 2006) and a greater tendency to change territories after a breeding failure (Harvey et al 1979, Haas 1998, Schjørring et al 2000, Sedgwick 2004). In addition, some birds change territories immediately after arrival, in response to local food depletion or other factors that are likely to reduce breeding success (Newton 2008).…”
mentioning
confidence: 99%